Prolongation (Orfeu, 2021)
The article evidences and documents the differences in meaning between the English term “prolongation”, the German Prolongation, and Schenker’s own understanding of the term. It stresses that, for Schenker, the word describes the organic relation from Ursatz to foreground, a relation in the “depth” of the work, while in English it denotes the extension in time of a harmonic or melodic event. The English understanding of “prolongation” is not illegitimate, but it hides a dimension of Schenker’s understanding.